2022
DOI: 10.1259/bjr.20220387
|View full text |Cite
|
Sign up to set email alerts
|

Image-mode performance characterisation of a positron emission tomography subsystem designed for Biology-guided radiotherapy (BgRT)

Abstract: Objectives: In this study, we characterize the imaging-mode performance of the positron emission tomography (PET) subsystem of the RefleXion X1 machine using the NEMA NU-2 2018 standard. Methods: The X1 machine consists of two symmetrically opposing 900 arcs of PET detectors incorporated into the architecture of a ring-gantry linear accelerator rotating up to 60 RPM. PET emissions from a tumor are detected by the PET detectors and used to guide the delivery of radiation beam. Imaging performance of the PET sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“… 1 , 2 The X1 system consists of an 85 cm O-ring gantry linear accelerator (linac) rotating at 60 rpm, a fan-beam kilovoltage computed tomography (kVCT) for image guidance of intensity modulated radiation therapy (IMRT) and stereotactic body radiation therapy (SBRT), and PET for real-time tumor tracking for biology-guided radiation therapy (BgRT). 3 The linac consists of a 6 MV flattening filter-free photon beam, a binary multileaf collimator (MLC) with 64 leaves, and 2 pairs of jaws located above and below the MLCs. The width of an MLC leaf is 6.25 mm at isocenter (85 cm from the source).…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 The X1 system consists of an 85 cm O-ring gantry linear accelerator (linac) rotating at 60 rpm, a fan-beam kilovoltage computed tomography (kVCT) for image guidance of intensity modulated radiation therapy (IMRT) and stereotactic body radiation therapy (SBRT), and PET for real-time tumor tracking for biology-guided radiation therapy (BgRT). 3 The linac consists of a 6 MV flattening filter-free photon beam, a binary multileaf collimator (MLC) with 64 leaves, and 2 pairs of jaws located above and below the MLCs. The width of an MLC leaf is 6.25 mm at isocenter (85 cm from the source).…”
Section: Introductionmentioning
confidence: 99%
“…The beam commissioning of the RefleXion X1 for intensity-modulated radiotherapy (IMRT)/stereotactic body radiotherapy (SBRT) was evaluated by Han et al 8 and the small field measurements and Monte Carlo simulations were performed by Shi et al 9 The treatment planning system was evaluated previously for IMRT and SBRT 10,11 and for BgRT. 12 The PET system characterization, calibration and quality assurance of RefleXion X1 was previously reported by Hu et al 13 where NEMA NU2-2018 standards were used to assess the PET image sensitivity, spatial resolution, scatter, count normalization, and image quality, in addition to the results of the daily PET quality assurance results. The PET subsystem sensitivity for X1 was measured at 0.183 and 0.161 cps/kBq at the center and off -center positions, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…A recently designed radiotherapy platform has incorporated an on-board kV fan-beam CT (kVCT) and Positron Emission Tomography (PET) system into a ring-shaped gantry that can provide both anatomical and functional images [8] . A few studies on this novel radiotherapy platform have been reported regarding the initial machine commissioning [9] , the characteristics of the PET imaging system performance [10] , treatment planning experiences [11] , [12] as well as a detailed clinical workflow for using this system for biology-guided radiotherapy [13] . However, the imaging performance of the kVCT system has not been investigated.…”
Section: Introductionmentioning
confidence: 99%